2018
DOI: 10.5430/jnep.v8n9p36
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ perception of psychological empowerment and its relationship to work engagement and job insecurity

Abstract: Background and objective: Psychological empowerment and work engagement are vital factors to consider when managing changes in workplace and enhancing both individual and overall organizational performance and increasing nurses' job security. This study aimed to explore how nurses perceive their psychological empowerment, work engagement, and job insecurity. Further, to investigate whether nurses' perception of psychological empowerment is related to their work engagement and job insecurity. Methods: A descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…Study was an empirical endeavor to explore upshot of psychological empowerment, work engagement with mediation of employee silence in public sector organizations. We devised based on previous studies available that psychological empowerment positively and significantly effects work engagement (Hashish et al, 2018;Nawrin, 2016) and study established the same results which are in line with previous studies (Hashish et al, 2018;Nawrin, 2016;Jose & Mampilly, 2014).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Study was an empirical endeavor to explore upshot of psychological empowerment, work engagement with mediation of employee silence in public sector organizations. We devised based on previous studies available that psychological empowerment positively and significantly effects work engagement (Hashish et al, 2018;Nawrin, 2016) and study established the same results which are in line with previous studies (Hashish et al, 2018;Nawrin, 2016;Jose & Mampilly, 2014).…”
Section: Discussionsupporting
confidence: 75%
“…Psychological empowerment enhances level of work engagement among employees in service sector (Hashish et al, 2018). Their findings supported to get benefit of work engagement by increasing psychological empowerment.…”
Section: Psychological Empowerment and Work Engagement In Services Sectormentioning
confidence: 64%
“…It could lead to reduce work stress of nurses and enhance quality of work life and improve their abilities to provide effective patient safety (Maslach & Leiter, 2016; Sarafis et al, 2016). Abou Hashish et al (2018) revealed that Egyptian nurses endorsed high level of psychological empowerment and work engagement and recognized a lower job insecurity level. Amarneh et al (2021) found that the psychological empowerment had a moderating effect on the relationship between work satisfaction and turnover intention among Jordanian registered nurses (RNs).…”
Section: Introductionmentioning
confidence: 99%
“…This finding was supported by several studies, which show that nurses have a moderate or satisfactory level of empowerment [12,14,[20][21][22][23]. Nonetheless, the result is inconsistent with the studies that indicate a high level of empowerment [5,6] or low level of empowerment among nurses [24]. This result might be explained by the hospitals' administration, characterized by a transformational leadership, which was found to be an effective leadership style that empowers the nursing staff.…”
Section: Discussionmentioning
confidence: 85%
“…In the nursing literature, a study conducted to assess nurses' perception of empowerment revealed that nurses experienced high psychological empowerment [5]. Nurses in this study perceived their work environment as empowering and their work as challenging and stimulating, requiring their competence [5]. Moreover, there are many studies in the literature that assess the relationship between nurses' empowerment and many nursing work-related factors.…”
Section: Introductionmentioning
confidence: 88%